Effectiveness and safety of anti-IL-5/Rα biologics in eosinophilic granulomatosis with polyangiitis: a two-year multicenter observational study - Nolasco, Santi; Portacci, Andrea; Campisi, Raffaele; Buonamico, Enrico; Pelaia, Corrado; Benfante, Alida; Triggiani, Massimo; Spadaro, Giuseppe; Caiaffa, Maria Filomena; Scioscia, Giulia; Detoraki, Aikaterini; Valenti, Giuseppe; et al. (Frontiers in Immunology, 2023)
Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare vasculitis characterized by asthma, systemic manifestations, and blood and tissue eosinophilia. Objective: To assess the effectiveness and safety of mepolizumab (anti-IL-5) and benralizumab (anti-IL-5Rα) in EGPA for 24 months. Methods: We conducted a multicenter observational study, including patients with EGPA treated with anti-IL-5/Rα biologics in 9 Italian specialized facilities. Systemic disease activity, remission and relapse rate were evaluated from 3 to 24 months after treatment initiation. Respiratory outcomes, hematological parameters, corticosteroid (OCS) and immunosuppressants consumption were also assessed. Results: 49 patients with relapsing-refractory EGPA were included [26 (53.1%) benralizumab 30mg, 20 (40.8%) mepolizumab 100mg, 3 (6.1%) mepolizumab 300mg]. Overall, 38.8% and 57.1% achieved remission after 12 and 24 months, respectively (69.2% benralizumab and 43.5% mepolizumab). Lower OCS intake and higher blood eosinophil count at baseline were associated with remission at 24 months. Both biologics exerted beneficial effects on severe asthma outcomes. Indeed, 61.2% (61.5% benralizumab and 60.8% mepolizumab) remained exacerbation-free during treatment. Lung function parameters showed improvements in the overall cohort (all p<0.05), but began to decline from month 12, especially with mepolizumab. Marked reduction in blood eosinophils was registered with mepolizumab (p<0.0001), while benralizumab depleted both eosinophils (p<0.0001) and basophils (p<0.0001). In general, 69.6% (76% benralizumab and 61.9% mepolizumab) of OCS-dependent patients lowered their daily dose by 75%, while 28.3% discontinued these drugs. Immunosuppressants were suspended in 88.2% of cases. Adverse events were reported in 8.2% of patients. Conclusions: These real-world data suggest that anti-IL-5/Rα biologics are effective and safe in the long-term as add-on treatments for patients with EGPA.